2020
DOI: 10.29407/js_unpgri.v6i2.14492
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas alat tes servis bolavoli berbasis mikrokontroller

Abstract: Ilmu pengetahuan dengan cepat harus menyesuaikan dengan tuntutan zaman. Berbagai cabang olahraga telah menggunakan kemajuan teknologi sebagai penunjang kegiatan baik dalam pembelajaran ataupun saat latihan khususnya pada olahraga cabang permainan bolavoli. Penelitian ini bertujuan untuk menguji efektivitas alat tes servis bolavoli berbasis mikrokontroller yang terdiri dari komponen-komponen seperti high performance, low power avr® 8-bit microcontroller unit, advanced risc architecture, high endurance non-volat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Based on the results of product validation in the form of a test tool for the upper and lower pass, a sensor-based volleyball game is suitable for use and then a revision of the model is carried out according to the advice given by the expert. This revision makes the test product better and more valid so that it could be applied to research subjects, other studies [21] concluded that this digital-based volleyball up-and-down passing ability test tool can be feasible or can be used, From these results, it can be interpreted that the volleyball bottom passing model for beginner athletes of Uniska MAB Banjarmasin students developed by researchers received a positive response and could be applied to beginner athletes of Uniska students [22] Other research on the development of volleyball tests is based on these results, it can be concluded that this microcontroller-based volleyball service test kit is effective of the beginners andprofessional athletes [23] based on the results of research and development of performance appraisal instruments with a peer rating system model in volleyball games that have been developed have met the validity requirements reliability and practicality, and is expected to be an evaluation tool that can be used [24], it can be concluded that the development of a sensor-based volleyball passing test is feasible based on the results of expert validation, [25] the results of the analysis became the basis for developing a sensor-based upper and lower pass test tool for volleyball games that would be given to research subjects, and this study for the first step to do the development of passing test.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of product validation in the form of a test tool for the upper and lower pass, a sensor-based volleyball game is suitable for use and then a revision of the model is carried out according to the advice given by the expert. This revision makes the test product better and more valid so that it could be applied to research subjects, other studies [21] concluded that this digital-based volleyball up-and-down passing ability test tool can be feasible or can be used, From these results, it can be interpreted that the volleyball bottom passing model for beginner athletes of Uniska MAB Banjarmasin students developed by researchers received a positive response and could be applied to beginner athletes of Uniska students [22] Other research on the development of volleyball tests is based on these results, it can be concluded that this microcontroller-based volleyball service test kit is effective of the beginners andprofessional athletes [23] based on the results of research and development of performance appraisal instruments with a peer rating system model in volleyball games that have been developed have met the validity requirements reliability and practicality, and is expected to be an evaluation tool that can be used [24], it can be concluded that the development of a sensor-based volleyball passing test is feasible based on the results of expert validation, [25] the results of the analysis became the basis for developing a sensor-based upper and lower pass test tool for volleyball games that would be given to research subjects, and this study for the first step to do the development of passing test.…”
Section: Discussionmentioning
confidence: 99%
“…Negara-negara maju saat ini telah banyak memanfaatkan teknologi sebagai penunjang prestasi atletnya. Contoh negara-negara maju yang sukses olahraganya dengan memanfaatkan ilmu pengetahuan dan teknologi seperti Amerika Serikat, Cina, Jepang, Jerman, dan negara lainnya (Giartama et al, 2020). Dengan kata lain, peningkatan dari kemampuan para atlet dapat dicapai lebih cepat dan lebih efisien dengan sentuhan dan perkembangan teknologi yang diterapkan, khususnya dalam melakukan latihan kebugaran fisik atlet.…”
unclassified